Understanding the Multidimensional and Dynamic Nature of Facial Expressions Based on Indicators for Appraisal Components as Basis for Measuring Drivers' Fear - Zhang, Meng; Ihme, Klas; Drewitz, Uwe; Jipp, Meike (Frontiers in Psychology, 2021)
Facial expressions are one of the commonly used implicit measurements for the in-vehicle affective computing. However, the time courses and the underlying mechanism of facial expressions so far have been barely focused on. According to the Component Process Model of emotions, facial expressions are the result of an individual’s appraisals, which are supposed to happen in sequence. Therefore, a multidimensional and dynamic analysis of drivers’ fear by using facial expression data could profit from a consideration of these appraisals. A driving simulator experiment with 37 participants was conducted, in which fear and relaxation were induced. It was found that the facial expression indicators of high novelty and low power appraisals were significantly activated after a fear event (high novelty: Z = 2.80, p < .01, rcontrast = 0.46; low power: Z = 2.43, p < .05, rcontrast = 0.50). Furthermore, after the fear event, the activation of high novelty occurred earlier than low power. These results suggest that multidimensional analysis of facial expression is suitable as an approach for the in-vehicle measurement of the drivers’ emotions. Furthermore, a dynamic analysis of drivers’ facial expressions considering of effects of appraisal components can add valuable information for the in-vehicle assessment of emotions.